AN ISSUES FACED BY FISHERMEN ON THE IMPLEMENTATION OF (STCW-F 1995): NORTHERN REGION OF MALAYSIA - Zoolfakar, Md Redzuan; Yahaya, Aminatul Hawa; Ab Rahman, Fauziah; Saifullah, Muhammad Dauud; Mohd Dahalan, Wardiah (International Journal of Supply Chain Management, 2018)
The STCW-F stand for Standards of Training, Certification and Watch keeping for Fishing Vessel Personnel, 1995 (STCW-F 1995), is set to enter into force on 29 September 2012. The 1995 STCW-F Convention sets the certification and minimum training requirements for crews of seagoing fishing vessels of 24 metres in length and above. Safety of fishermen is one of the STCW-F objectives and to prevent casualties during at sea. Thus implementation of STCW-F in Malaysia fishery industry is a must, but before authorities/government want to implement this convention to fishermen, issues faced by fishermen are important to discover so that authorities/government may counter when the issues take place. This paper used statistical analysis such as chi-square test, friedman test, wilcoxon signed ranks test and bonferroni correction to extract the variables that have been collected from fishermen using questionnaires. The finding major fishermen significantly agree all factors are related to each other if government want to implement the convention for example, fishermen awareness, government roles, consequences of implementation, cost and fees and lack of training center. The biggest challenges for fishermen on this implementation is cost and fees. The factors that has been extract with statistical analyses shows the issues faced by fishermen on the implementation of STCW-F 1995.